Ontogenetic development of digestive enzymes in larval and juvenile crimson snapper Lutjanus erythopterus (Bloch 1790). (4th February 2017) - Cui, Ke; Cheng, Dachuan; Ma, Zhenhua; Qin, Jian G.; Jiang, Shigui; Sun, Dianrong; Ma, Shengwei
Abstract: Ontogenetic development of digestive system in crimson snapper ( Lutjanus erythopterus Bloch 1790) larvae was histologically and enzymatically (alkaline phosphatase, amylase, lipase, pepsin, trypsin) examined from hatching to 36 days post hatching (DPH). The ontogenetic development of crimson snapper larval fish ontogeny was divided into three distinct phases: phase I starting from hatch to the onset of exogenous feeding, phase II starting from first feeding (2–3 DPH) until the formation of gastric glands (13–14 DPH) and phase III beginning from the appearance of gastric glands and continuing onwards. The specific activities of amylase, lipase, trypsin showed sharp increase and reached to the maximum from hatch to 4 DPH, 10 DPH, 20 DPH, respectively, followed by a declining trend with irregular fluctuation. In contrast to other enzymes, the specific activities of alkaline phosphatase showed a gradual increase from hatch to 29 DPH, followed by a sharp increase towards 36 DPH. The specific activity of pepsin was firstly detected on 17 DPH and gradually increased towards the end of this study. The total activities of these five enzymes showed a gradual increase till 29 DPH, followed by a sharp increase towards 36 DPH except for amylase and lipase reaching maximum at 32 DPH. The present study provides better understanding of the digestive ontogeny of crimson snapper during the larval stage and a guide to feeding and weaning of this economically important fish in hatcheries.